Socioeconomic Status and Prognosis of Patients With ST-Elevation Myocardial Infarction Managed by the Emergency-Intervention “Codi IAM” Network - Tizón-Marcos, Helena; Vaquerizo, Beatriz; Ferré, Josepa Mauri; Farré, Núria; Lidón, Rosa-Maria; Garcia-Picart, Joan; Regueiro, Ander; Ariza, Albert; Carrillo, Xavier; Duran, Xavier; Poirier, Paul; Cladellas, Mercè; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Despite the spread of ST-elevation myocardial infarction (STEMI) emergency intervention networks, inequalities in healthcare access still have a negative impact on cardiovascular prognosis. The Family Income Ratio of Barcelona (FIRB) is a socioeconomic status (SES) indicator that is annually calculated. Our aim was to evaluate whether SES had an effect on mortality and complications in patients managed by the “Codi IAM” network in Barcelona. Methods This is a cohort study with 3,322 consecutive patients with STEMI treated in Barcelona from 2010 to 2016. Collected data include treatment delays, clinical and risk factor characteristics, and SES. The patients were assigned to three SES groups according to FIRB score. A logistic regression analysis was conducted to estimate the adjusted effect of SES on 30-day mortality, 30-day composite cardiovascular end point, and 1-year mortality. Results The mean age of the patients was 65 ± 13% years, 25% were women, and 21% had diabetes mellitus. Patients with low SES were younger, more often hypertensive, diabetic, dyslipidemic (p < 0.003), had longer reperfusion delays (p < 0.03) compared to participants with higher SES. Low SES was not independently associated with 30-day mortality (OR: 0.95;9 5% CI: 0.7–1.3), 30-day cardiovascular composite end point (OR: 1.03; 95% CI: 0.84–1.26), or 1-year all-cause mortality (HR: 1.09; 95% CI: 0.76–1.56). Conclusion Although the low-SES patients with STEMI in Barcelona city were younger, had worse clinical profiles, and had longer revascularization delays, their 30-day and 1-year outcomes were comparable to those of the higher-SES patients.